Repeated high-intensity technique training and repeated sprint training elicit similar adjustment in physiological tesponses but fivergent perceptual responses and combat-related performances in adolescent taekwondo matches - Ouergui, I.; Delleli, S.; Messaoudi, H.; Bridge, C. A.; Chtourou, H.; Franchini, E.; Ardigò, L. P. (International Journal of Sports Physiology and Performance, 2023)
Purpose: This study investigated the effects of 4 weeks of repeated sprint training (RST) versus repeated high-intensity technique training (RTT) on the physiological responses (ie, blood lactate), mean and peak heart rate, rating of perceived exertion, technical-tactical performance, and time-motion variables during simulated taekwondo combats.